Photocatalytic Cu2O and SnS2 composite material as well as preparation method and application thereof

The synthesis of Cu2O@SnS2 composite material by hydrothermal method solved the problems of low catalytic performance and insufficient stability of existing photocatalysts, achieved the effect of efficient degradation of organic pollutants in water, and maintained good cycle stability.

CN119425729AActive Publication Date: 2025-02-14GUANGDONG UNIV OF PETROCHEMICAL TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411330817.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

When existing photocatalysts catalyze the degradation of organic pollutants in water, their catalytic performance is low and their stability is insufficient, making it difficult to effectively treat organic pollutants in water.

Method used

Cu2O@SnS2 composite material was synthesized by hydrothermal method, and Cu2O positive cube crystals were evenly distributed on the petal-shaped SnS2 surface to form a photocatalytic composite material with high catalytic properties and good stability.

Benefits of technology

The degradation rate of Cu2O@SnS2 composite material of organic pollutants in water reaches more than 90% under light, and the degradation efficiency of 90% remains after 4 cycles of degradation, which significantly improves the photocatalytic effect and stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425729A_ABST
    Figure CN119425729A_ABST
Patent Text Reader

Abstract

The invention discloses a photocatalytic Cu2O and SnS2 composite material as well as a preparation method and application thereof, and aims to provide the photocatalytic Cu2O and SnS2 composite material which has relatively high photocatalytic performance and relatively good stability, can effectively treat organic pollutants in water, and can still keep the degradation rate at 90% or above after four times of cyclic degradation. According to the technical scheme, the composite photocatalytic material is prepared from a cubic crystalline Cu2O material and a petal-shaped SnS2 material, wherein the cubic crystalline Cu2O material is uniformly distributed on the surface of the petal-shaped SnS2 material to form the composite photocatalytic material; belongs to the technical field of inorganic material synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic degradation, and in particular to a photocatalytic Cu2O@SnS2 composite material. The present invention also relates to a preparation method and application of the material. Background Art

[0002] With the rapid progress of society and the continuous development of science and technology, environmental issues and energy crises have gradually attracted great attention from people. Among them, water pollution is particularly serious, and dye wastewater is a typical representative. The soluble and insoluble pigments in dye wastewater are dispersed in water, making the water quality present various colors, which seriously affects the safety and sustainable use of water resources. Photocatalytic technology uses clean and renewable sunlight as a driving force. In recent years, photocatalytic oxidation has achieved remarkable results in alleviating water pollution, showing the characteristics of high efficiency, cleanliness and greenness. Nano-scale catalysts perform well in the photocatalytic degradation process and have higher degradation efficiency for colored pollutants. This breakthrough not only improves the efficiency of pollutant treatment, but also provides new ideas and means for solving water pollution problems. With the continuous advancement of science and technology and the increasing attention of society to environmental protection, photocatalytic technology has broad application prospects in the field of water pollution control and will make greater contributions to solving environmental pollution problems such as dye wastewater.

[0003] For example, Chinese patent 103623845A discloses a method for preparing a nano-composite photocatalyst for treating hexavalent chromium wastewater, which comprises: 1) mixing and dissolving an aqueous solution of thioacetamide, tin tetrachloride pentahydrate and citric acid monohydrate, placing the mixture in a stainless steel autoclave lined with polytetrafluoroethylene, sealing the mixture and placing the mixture in an electric oven, heating the mixture at 140°C for 12 hours, stopping the heating and cooling the mixture naturally to room temperature, filtering out the precipitate obtained by the reaction, washing the mixture with deionized water and drying the mixture in a vacuum drying oven at 100°C to obtain SnS2 nanoparticles; 2) ultrasonically dispersing the SnS2 nanoparticles in water to form a SnS2 suspension; 3) mixing and reacting an aqueous solution of copper acetate and the SnS2 suspension, filtering out the precipitate obtained by the reaction, washing the mixture with deionized water and drying the mixture in a vacuum drying oven at 100°C to obtain a nano-composite photocatalyst. The method first prepares SnS2 nanoparticles, and then reacts with copper acetate water to obtain SnS2 / CuS nanocomposite photocatalyst material; the nanocomposite photocatalyst is a solid nanomaterial with a small catalyst contact area and unsatisfactory catalytic performance.

[0004] Therefore, it is particularly necessary to develop a catalyst with high photocatalytic performance and good stability for effectively treating organic pollutants in water. Summary of the invention

[0005] In order to solve the above problems, the purpose of the present invention is to provide a photocatalytic Cu2O@SnS2 composite material, which has high photocatalytic performance and good stability, and can effectively treat organic pollutants in water. After 4 cycles of degradation, the degradation rate can still be maintained above 90%.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned photocatalytic Cu2O@SnS2 composite material.

[0007] The second object of the present invention is to provide an application of the above-mentioned photocatalytic Cu2O@SnS2 composite material.

[0008] The first technical solution provided by the present invention is as follows:

[0009] A photocatalytic Cu2O@SnS2 composite material comprises a cubic crystalline Cu2O material and a petal-shaped SnS2 material. The cubic crystalline Cu2O material is uniformly distributed on the surface of the petal-shaped SnS2 to form a composite photocatalytic material.

[0010] Furthermore, in the above-mentioned photocatalytic Cu2O@SnS2 composite material, cubic crystalline Cu2O is directly synthesized on petal-shaped SnS2.

[0011] The second technical solution provided by the present invention is as follows:

[0012] A method for preparing a photocatalytic Cu2O@SnS2 composite material comprises the following steps in sequence:

[0013] S1: Dissolve thioacetamide (TAA) and SnCl4·5H2O in an ethanol solution at room temperature, stir evenly, then transfer the reaction solution to a hydrothermal synthesis reactor, perform a hydrothermal reaction at 150-200°C for 10-16h, cool the product to room temperature after the reaction, collect the precipitate by centrifugation, wash the collected precipitate, and vacuum dry it to obtain a SnS2 solid material;

[0014] S2: Dissolve CuSO4·5H2O, sodium citrate and the petal-shaped SnS2 solid obtained in S1 in deionized water at room temperature and stir evenly to obtain a mixed solution A. Add sodium hydroxide solution to the mixed solution A to obtain a suspension. Add L-ascorbic acid solution to the suspension and stir evenly to obtain a mixed solution B. Age the mixed solution B at room temperature for 1 h, collect the precipitate by centrifugation, wash the collected precipitate, and then vacuum dry to obtain a photocatalytic Cu2O@SnS2 composite.

[0015] Furthermore, in the above-mentioned method for preparing a photocatalytic Cu2O@SnS2 composite material, the amount of TAA described in S1 is 0.8-1.5 g; the amount of SnCl4·5H2O described is 0.5-0.9 g; and the volume of the ethanol solution is 60-100 mL.

[0016] Furthermore, in the preparation method of the above-mentioned photocatalytic Cu2O@SnS2 composite material, the amount of CuSO4·5H2O in S2 is 0.3~0.6g; the amount of sodium citrate is 0.1~0.3g; the amount of the petal-shaped SnS2 solid obtained in S1 is 0.06~1.00g; the volume of the deionized water is 60~100mL; the concentration of the sodium hydroxide solution is 0.5~2mol·L -1 , the volume is 10 to 30 mL; the concentration of the L-ascorbic acid solution is 20 to 40 mol·mL -1 , the volume is 40~60mL.

[0017] Furthermore, in the above-mentioned method for preparing a Cu2O@SnS2 composite material, in S1: the stirring time is 25 to 40 minutes, and the magnetic stirring time is 3 to 8 minutes.

[0018] Furthermore, in the above-mentioned method for preparing a photocatalytic Cu2O@SnS2 composite material, when S1, S2, S3, and S3 are dried, the vacuum degree is 2500kPa, the temperature is 50-70°C, and the time is 10-16h.

[0019] Furthermore, in the above-mentioned method for preparing a photocatalytic Cu2O@SnS2 composite material, the washing described in S1 and S2 is first centrifugally washing with deionized water for 2 to 3 times, and then washing with ethanol for 2 to 3 times.

[0020] The third technical solution provided by the present invention is the application of the above-mentioned photocatalytic Cu2O@SnS2 composite material as a photocatalyst.

[0021] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages:

[0022] 1. The composite material Cu2O cubic crystal material provided by the present invention is evenly distributed on the surface of petal-shaped SnS2 to form a photocatalytic Cu2O@SnS2 composite material. The petal-shaped structure has a large catalyst contact area and high catalytic degradation performance. After illumination, the degradation rate of Cu2O@SnS2 can reach 90%, indicating that the Cu2O@SnS2 composite material can effectively improve the photocatalytic effect of the material.

[0023] 2. The technical solution provided by the present invention has cheap raw materials and can efficiently utilize solar energy resources to degrade organic pollutants, and has potential application prospects in environmental protection and wastewater treatment.

[0024] 3. The technical solution provided by the present invention is a method combining simple chemical reaction synthesis and hydrothermal method, and then growing Cu2O cubic crystal nanostructure on the surface of petal-shaped SnS2 by hydrothermal method to obtain a photocatalytic Cu2O@SnS2 composite material, which has a simple preparation process and is easy to industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the SEM image of the photocatalytic Cu2O@SnS2 composite material prepared in Example 1;

[0026] Figure 2 SEM images of the photocatalytic Cu2O@SnS2 composite materials prepared in Examples 2 to 4;

[0027] Figure 3 This is the degradation rate of methylene orange (MO) by different catalysts under full light irradiation;

[0028] Figure 4 The recycling performance of the photocatalytic Cu2O@SnS2 composite catalyst;

[0029] Figure 5 This is the degradation rate of methylene orange (MO) under full light irradiation with different catalyst contents. DETAILED DESCRIPTION

[0030] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.

[0031] Example 1

[0032] The present embodiment provides a photocatalytic Cu2O@SnS2 composite material, which is prepared by the following method:

[0033] 1) 1.0 g of thioacetamide (TAA) and 0.7 g of SnCl4·5H2O were dissolved in an ethanol solution at room temperature and stirred evenly for 5 min. The reaction solution was then transferred to a hydrothermal synthesis reactor and subjected to a hydrothermal reaction at 160° C. for 12 h. After the reaction was completed, the product was cooled to room temperature and the precipitate was collected by centrifugation. The precipitate was washed three times with water and three times with ethanol. The collected precipitate was then washed and dried under vacuum at 60° C. for 12 h to obtain a SnS2 solid material.

[0034] 2) 0.375 g CuSO4·5H2O and 0.147 g sodium citrate and 0.08 g SnS2 petal-shaped solid material obtained in step 1) were dissolved in deionized water at room temperature and stirred uniformly to obtain a mixed solution A, 20 mL 1.25 mol / L sodium hydroxide solution was added to the mixed solution A to obtain a suspension, and 50 mL 0.03 mol / L L-ascorbic acid solution was added to the suspension and stirred for 3 min to obtain a mixed solution B, the mixed solution B was aged at room temperature 25°C for 1 h, the precipitate was collected by centrifugation, washed three times with water and three times with ethanol, and the collected precipitate was washed and dried in vacuum at 60°C for 12 h to obtain a photocatalytic Cu2O@SnS2 composite, the SEM image of which is shown in Figure 1 .

[0035] Example 2

[0036] The present embodiment provides a photocatalytic Cu2O@SnS2 composite material, which is prepared by the following method:

[0037] 1) 0.9 g of thioacetamide (TAA) and 0.9 g of SnCl4·5H2O were dissolved in an ethanol solution at room temperature and stirred evenly for 5 min. The reaction solution was then transferred to a hydrothermal synthesis reactor and subjected to a hydrothermal reaction at 160° C. for 12 h. After the reaction was completed, the product was cooled to room temperature and the precipitate was collected by centrifugation. The precipitate was washed three times with water and three times with ethanol. The collected precipitate was then washed and dried in vacuum at 60° C. for 12 h to obtain a SnS2 solid material.

[0038] 2) 0.6 g Cu SO4·5H2O and 0.3 g sodium citrate and 1.0 g SnS2 petal-shaped solid material obtained in step 1) were dissolved in deionized water at room temperature and stirred uniformly to obtain a mixed solution A, 30 mL 2 mol / L sodium hydroxide solution was added to the mixed solution A to obtain a suspension, and 60 mL 30 mol / L ascorbic acid solution was added to the suspension and stirred for 3 min to obtain a mixed solution B, the mixed solution B was aged at room temperature 25°C for 1 h, the precipitate was collected by centrifugation, washed three times with water and three times with ethanol, and the collected precipitate was washed and vacuum dried at 60°C for 12 h to obtain a photocatalytic Cu2O@SnS2 composite, the SEM image of which is shown in FIG. Figure 2 (a).

[0039] Example 3

[0040] The present embodiment provides a photocatalytic Cu2O@SnS2 composite material, which is prepared by the following method:

[0041] 1) 0.8 g of thioacetamide (TAA) and 0.5 g of SnCl4·5H2O were dissolved in an ethanol solution at room temperature and stirred evenly for 5 min. The reaction solution was then transferred to a hydrothermal synthesis reactor and subjected to a hydrothermal reaction at 160° C. for 12 h. After the reaction was completed, the product was cooled to room temperature and the precipitate was collected by centrifugation. The precipitate was washed three times with water and three times with ethanol. The collected precipitate was then washed and dried in vacuum at 60° C. for 12 h to obtain a SnS2 solid material.

[0042] 2) 0.3 g CuSO4·5H2O and 0.1 g sodium citrate and 0.06 g SnS2 petal-shaped solid material obtained in step 1) were dissolved in deionized water at room temperature and stirred uniformly to obtain a mixed solution A, 10 mL 0.5 mol / L sodium hydroxide solution was added to the mixed solution A to obtain a suspension, and 40 mL 0.02 mol / L L-ascorbic acid solution was added to the suspension and stirred for 3 min to obtain a mixed solution B, the mixed solution B was aged at room temperature 25°C for 1 h, the precipitate was collected by centrifugation, washed three times with water and three times with ethanol, and the collected precipitate was washed and dried at 60°C in vacuum for 12 h to obtain a photocatalytic Cu2O@SnS2 composite, the SEM image of which is shown in FIG. Figure 2 (b).

[0043] Example 4

[0044] The present embodiment provides a photocatalytic Cu2O@SnS2 composite material, which is prepared by the following method:

[0045] 1) 1.0 g of thioacetamide (TAA) and 0.7 g of SnCl4·5H2O were dissolved in an ethanol solution at room temperature and stirred evenly for 5 min. The reaction solution was then transferred to a hydrothermal synthesis reactor and subjected to a hydrothermal reaction at 160° C. for 12 h. After the reaction was completed, the product was cooled to room temperature and the precipitate was collected by centrifugation. The precipitate was washed three times with water and three times with ethanol. The collected precipitate was then washed and dried under vacuum at 70° C. for 16 h to obtain a SnS2 solid material.

[0046] 2) 0.375 g CuSO4·5H2O and 0.147 g sodium citrate and 0.08 g SnS2 petal-shaped solid material obtained in step 1) were dissolved in deionized water at room temperature and stirred uniformly to obtain a mixed solution A, 20 mL 1.25 mol / L sodium hydroxide solution was added to the mixed solution A to obtain a suspension, and 50 mL 0.03 mol / L ascorbic acid solution was added to the suspension and stirred for 3 min to obtain a mixed solution B, the mixed solution B was aged at room temperature 25°C for 1 h, the precipitate was collected by centrifugation, washed three times with water and three times with ethanol, and the collected precipitate was washed and dried at 70°C in vacuum for 16 h to obtain a photocatalytic Cu2O@SnS2 composite, the SEM image of which is shown in FIG. Figure 2 (c).

[0047] Example 5

[0048] The present embodiment provides a photocatalytic Cu2O@SnS2 composite material, which is prepared by the following method:

[0049] 1) 1.0 g of thioacetamide (TAA) and 0.7 g of SnCl4·5H2O were dissolved in an ethanol solution at room temperature and stirred evenly for 5 min. The reaction solution was then transferred to a hydrothermal synthesis reactor and subjected to a hydrothermal reaction at 160° C. for 12 h. After the reaction was completed, the product was cooled to room temperature and the precipitate was collected by centrifugation. The precipitate was washed three times with water and three times with ethanol. The collected precipitate was then washed and dried under vacuum at 70° C. for 16 h to obtain a SnS2 solid material.

[0050] 2) 0.375 g CuSO4·5H2O and 0.147 g sodium citrate and 0.08 g SnS2 petal-shaped solid material obtained in step 1) were dissolved in deionized water at room temperature and stirred uniformly to obtain a mixed solution A, 20 mL 1.25 mol / L sodium hydroxide solution was added to the mixed solution A to obtain a suspension, and 50 mL 0.03 mol / L L-ascorbic acid solution was added to the suspension and stirred for 3 min to obtain a mixed solution B, the mixed solution B was aged at room temperature 25°C for 1 h, the precipitate was collected by centrifugation, washed three times with water and three times with ethanol, and the collected precipitate was washed and dried in vacuum at 70°C for 16 h to obtain a photocatalytic Cu2O@SnS2 composite, the SEM image of which is shown in Figure 2 (d).

[0051] In order to prove the effect of the technical solution provided by this application, the experimental data of its photocatalytic degradation performance test are given below:

[0052] 1. Degradation efficiency of methylene orange (MO) by photocatalytic Cu2O@SnS2 composite material.

[0053] 24 mg of Cu2O cubic crystals, 24 mg of SnS2 nanoparticles and 24 mg of Cu2O@SnS2 catalyst were added to 60 mL of methylene orange (MO). After stirring in the dark for 15 minutes, the degradation rates of Cu2O cubic crystals, SnS2 nanoparticles and composite Cu2O@SnS2 were 64.4%, 55.1% and 80.6%, respectively. Obviously, the degradation rate of methylene orange (MO) by Cu2O@SnS2 is higher than that of other substances. Moreover, after 15 minutes of illumination, the degradation rate of Cu2O@SnS2 is as high as 80%, which shows that the photocatalytic effect of the material can be effectively improved by constructing the composite Cu2O@SnS2; Figure 3 shown.

[0054] 15 mg of the photocatalytic Cu2O@SnS2 complex prepared in Example 1, 18 mg of the photocatalytic Cu2O@SnS2 complex prepared in Example 1, 24 mg of the photocatalytic Cu2O@SnS2 complex prepared in Example 1, 30 mg of the photocatalytic Cu2O@SnS2 complex prepared in Example 1, and 60 mg of the photocatalytic Cu2O@SnS2 complex prepared in Example 1 were added to 60 mL of methylene orange (MO), and then degraded for 60 min under full light irradiation of a 300 W xenon lamp, and samples were taken every 5 min to test their absorbance. The results are as follows Figure 5 As shown in the figure, after 5 minutes of stirring and degradation in the dark, the degradation rates of Cu2O, SnS2 and Cu2O@SnS2 composite were 55.1%, 64.4% and 94.7% respectively. After 90 minutes of full light irradiation, the degradation rates of Cu2O, SnS2 and Cu2O@SnS2 composite were 55.1%, 64.4% and 94.7% respectively. The degradation rate of MO by Cu2O@SnS2 composite was significantly higher than that of Cu2O and SnS2. It is speculated that this is mainly due to the fact that after Cu2O and SnS2 are combined, they have a larger specific surface area and more active sites to achieve higher degradation efficiency.

[0055] The photocatalytic degradation rate of the Cu2O@SnS2 nanocomposite prepared in Example 1 of the present invention is shown in FIG. Figure 4 As shown, from Figure 5 It can be seen that after 60 minutes of illumination, the degradation rate is 80.4% when the content is 15 mg, 85.8% when the content is 18 mg, 92.2% when the content is 24 mg, 92.9% when the content is 30 mg, and 93% when the content is 60 mg. Under the same illumination time, the degradation rate when the content is 30 mg is greater than the degradation rates when the content is 15 mg, 18 mg, 24 mg, and 60 mg, which shows that when the content of Cu2O@SnS2 is 30 mg, it is the best catalyst content for this degradation process.

[0056] 2. Photocatalytic cycle performance

[0057] The cyclic stability of photocatalysts is one of the key indicators for practical applications. When the concentration of methylene orange (MO) in aqueous solution reaches a certain value, it will cause a series of harms to the human body. This experiment takes methylene orange (MO) as the object and performs photocatalytic degradation under full light irradiation. Therefore, it is necessary to study the cyclic degradation efficiency of methylene orange (MO) on Cu2O@SnS2 under simulated sunlight. Sunlight is simulated by xenon lamp irradiation. The operation is to take 24 mg of the catalyst prepared in Example 3, disperse it in 60 mL of 15 mg / L methylene orange (MO) solution, stir it magnetically (dark environment) for 1 min, turn on the xenon lamp light source, and keep the solution environment temperature stable by external circulating water. Take 4.5 ml of the mixed solution every 5 min, centrifuge and filter the supernatant, measure the absorbance value at the maximum absorption wavelength (k=664 nm), collect the precipitate again by centrifugation, wash it 3 times with deionized water by centrifugation, and then wash it 3 times with ethanol. Figure 4 As shown in the figure, after 4 cycles of degradation, the degradation efficiency of Cu2O@SnS2 can still be maintained above 90%, indicating that the Cu2O@SnS2 composite structure can still maintain a certain degree of crystallinity and Cu2O@SnS2 has good photocatalytic degradation stability.

Claims

1. A photocatalytic Cu2O@SnS2 composite material, characterized in that: It includes cubic crystalline Cu2O material and petal-shaped SnS2 material. The cubic crystalline Cu2O material is evenly distributed on the surface of the petal-shaped SnS2 to form a composite photocatalytic material.

2. The photocatalytic Cu2O@SnS2 composite material according to claim 1, characterized in that: Cubic Cu2O was directly synthesized on petal-shaped SnS2.

3. A method for preparing a photocatalytic Cu2O@SnS2 composite material, characterized in that: The steps are as follows: S1: Dissolve thioacetamide and SnCl4·5H2O in an ethanol solution at room temperature, stir evenly, then transfer the reaction solution to a hydrothermal synthesis reactor, perform a hydrothermal reaction at 150-200°C for 10-16h, cool the product to room temperature after the reaction, collect the precipitate by centrifugation, wash the collected precipitate, and vacuum dry it to obtain a petal-shaped SnS2 solid material; S2: Dissolve CuSO4·5H2O, sodium citrate and the petal-shaped SnS2 solid obtained in S1 in deionized water at room temperature and stir evenly to obtain a mixed solution A. Add sodium hydroxide solution to the mixed solution A to obtain a suspension. Add L-ascorbic acid solution to the suspension and stir evenly to obtain a mixed solution B. Age the mixed solution B at room temperature for 1 h, collect the precipitate by centrifugation, wash the collected precipitate, and then vacuum dry to obtain a photocatalytic Cu2O@SnS2 composite.

4. The method for preparing a photocatalytic Cu2O@SnS2 composite material according to claim 3, characterized in that: The amount of thioacetamide in S1 is 0.8-1.5 g; the amount of SnCl4·5H2O is 0.5-0.9 g; and the volume of the ethanol solution is 60-100 mL.

5. The method for preparing a photocatalytic Cu2O@SnS2 composite material according to claim 3, characterized in that: The amount of CuSO4·5H2O in S2 is 0.3-0.6 g; the amount of sodium citrate is 0.1-0.3 g; the amount of the petal-shaped SnS2 solid obtained in S1 is 0.06-1.00 g; the volume of deionized water is 60-100 mL; the concentration of the sodium hydroxide solution is 0.5-2 mol·L -1 , the volume is 10 to 30 mL; the concentration of the L-ascorbic acid solution is 20 to 40 mol·mL -1 , the volume is 40~60mL.

6. The method for preparing a photocatalytic Cu2O@SnS2 composite material according to claim 3, characterized in that: In S1: the stirring time is 25 to 40 minutes, and the magnetic stirring time is 3 to 8 minutes.

7. The method for preparing a photocatalytic Cu2O@SnS2 composite material according to claim 3, characterized in that: When S1 and S2 are dried, the vacuum degree is 2500 kPa, the temperature is 50-70° C., and the time is 10-16 h.

8. The method for preparing a photocatalytic Cu2O@SnS2 composite material according to claim 3, characterized in that: The washing described in S1 and S2 is first centrifugally washing with deionized water for 2-3 times, and then washing with ethanol for 2-3 times.

9. Use of the photocatalytic Cu2O@SnS2 composite material as claimed in claim 1 as a photocatalyst.

Citation Information

Patent Citations

  • Small-size cube nanometer cuprous oxide preparation method

    CN107601548A

  • Flexible carbon fiber cloth@Cu2O@SnS2 composite material, preparation method and application

    CN111389418A

  • Cuprous oxide / molybdenum disulfide composite material as well as preparation method and application thereof

    CN111468143A

  • CuS-coated SnS2 composite material with cubic hollow core-shell structure as well as preparation method and application of CuS-coated SnS2 composite material

    CN117797831A